Effect of Solvent Composition on the Critical Micelle Concentration of Cetylpyridinium Chloride in Ethanol-Water Mixed Solvent Media - Bhattarai, Ajaya; Shah, Sujit Kumar; Yadav, Ashok Kumar (Nepal Journal of Science and Technology, 2013)
The accurate measurement of the specific conductivity of cetylpyridinium chloride in pure water and ethanol-water mixed solvent media containing 0.10, 0.20, 0.30 and 0.40 volume fraction of ethanol at room temperature are reported. The concentrations were varied from ~ 0.005 mol l-1 to ~ 0.0002 mol l-1.The conductivity of cetylpyridinium chloride decreases with the increase in the volume fraction of ethanol. The critical micelle concentration of cetylpyridinium chloride increases with the increase in the volume fraction of ethanol. Nepal Journal of Science and Technology Vol. 13, No. 1 (2012) 89-93 DOI: http://dx.doi.org/10.3126/njst.v13i1.7446